E-BUSINESS TO SUPPORT SALES OF FARMER CROPS BASED ON MOBILE APPLICATIONS - Muhammad Aiman Abdul Hafizh; Ari Purno Wahyu Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The agricultural sector is essential because it is the leading sector and supports the Indonesian economy. Sukapura Village is one of the producers of plant products in the Kertasari District. But on the other hand, most of the farmers experienced problems, and several obstacles emerged, such as the accumulation of harvests that were sold at low prices, which resulted in losses, and the difficulty of distribution because it was pretty complicated. Of course, this situation must be improved so that people can enjoy Indonesian agricultural products. One of them is by building an android-based application